The association of the expression of calcium handling proteins and their polymorphic variants of genes with the structural and functional state of the heart of patients with atrial fibrillation. (24th May 2021) - Kondrat"eva, D; Afanasiev, SA; Muslimova, EF; Archakov, EA; Batalov, RE
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): The Russian Science Foundation, the Cardiology Research Institute, Tomsk National Research Medical Center of the Russian Academy of Sciences. Background. The cellular mechanisms of the genesis of atrial fibrillation are associated with impaired intracellular transport of calcium ions, which is determined by the activity of calcium-transporting proteins of the sarcoplasmic reticulum (SR). The aim of the study to investigate the expression of calcium handling proteins of the sarcoplasmic reticulum and their polymorphic variants of genes with the structural and functional state of the heart of patients with permanent atrial fibrillation. Methods. The study included 45 patients aged 29 to 65 years with atrial fibrillation. A complete echocardiographic study was performed according to standard views (parasternal and apical views) by an En Visor CHD Philips sonograph (Netherlands). All patients underwent catheter ablation, during which a biopsy of myocardial tissue from the top of the left ventricle (1-3 mg) was taken. The protein content of SERCA2a and calsequestrin (CASQ2) was determined by immunoblotting in patient's myocardium. We identified polymorphic variants rs1860561 of the SERCA2a and rs6684209 and rs7521023 of the CASQ2 gene by real-time polymerase chain reaction. Results. The expression of both SERCA2a and CASQ2 proteins correlated with the size of the left atrium (LA). Thus, a higher level of SERCA2a expression in the myocardium corresponded to a larger LA size in patients. Despite the fact that the LV ejection fraction did not correlate with the expression level of the studied proteins, a direct correlation was found between the SERCA2a level and the values of LV end-diastolic and systolic volumes. In addition, the hemodynamic parameters of the heart, characterizing the diastolic function of the heart of patients, such as the rates of early (peak E) and late diastolic filling (peak A) LV were lower in patients with a higher SERCA2a level, although the ratio of these parameters (peak E/peak A) had no significant differences. In the homozygous GG genotype of the ATP2A2 gene, the expression level of the SERCA2a protein was (p = 0.039) higher than in patients with the heterozygous genotype (GA). Analysis of the parameters of the ECHO-KG study showed that the presence of the A allele of the rs1860561 variant of the ATP2A2 gene is associated with an increase in the LV sphericity index. The expression of the CASQ2 protein in patients with CC genotype of the rs6684209 variant of the CASQ2 gene was 2.5 times higher than in patients with CT genotype. The genotypes of the rs7521023 variant of the CASQ2 gene were not associated with the level of expression of the corresponding protein in the myocardium of the studied patients. Conclusions. The different genotypes of the rs1860561 variant of the ATP2A2 gene and rs6684209 of the CASQ2 gene can modulate the expression level of the SERCA2a protein and the CASQ2 protein. Moreover, the expression of calcium handling proteins to a greater extent affects the functional and structural characteristics of the heart of patients with permanent AF.